Hydrogen-bonded supramolecular architectures based on [Zr(C2O4)4]4− anion and protonated polyamine cations. Issue 12 (6th March 2017) - Hamdouni, Monia; Walha, Siwar; Duhayon, Carine; Kabadou, Ahlem; Sutter, Jean-Pascal
Abstract : Extended supramolecular architectures based on ionic H-bond association between [Zr(C2 O4 )4 ] 4− and various cationic linear or crooked amine derivatives are reported. Abstract : A series of protonated polyamine derivatives have been considered as H-bond donor units for the construction of extended networks by assemblage with the anionic metal-oxalate complex [Zr(C2 O4 )4 ] 4− by means of charge-assisted H-bonds. In order to evaluate the parameters that favor the formation of 3D open-framework architectures, linear, flexible and V-shaped organic cations (H n -L x ) y + have been selected. Four different compounds of the formula [(H2 -L1)2 Zr(C2 O4 )4 ]·2H2 O, 1, [(H2 -L2)2 Zr(C2 O4 )4 ]·4H2 O, 2, [(H2 -L3)2 Zr(C2 O4 )4 ]·4H2 O, 3, and [(H-L4)4 Zr(C2 O4 )4 ]·2H2 O, 4 (with L1 = thiocarbohydrazide, L2 = ortho -phenylene diamine, L3 = piperazine and L4 = 4-aminopyridine) are reported. Depending on the cations' shape, 2D to 3D H-bonded networks have been characterized. The crystal structures of all four architectures as well as their thermal stabilities are reported. The dominant intermolecular interactions and their directionality have been examined by Hirshfeld surfaces and fingerprint analysis.